Urban vectors of Chagas disease in the American continent: A systematic review of epidemiological surveys. - Ana Laura Carbajal-; Paz Sánchez-Casaccia; Romina Valeria Piccinali; Yael Provecho; Liliana Salvá; Sergio Meli; Florencia Cano; Ricardo Hernández; Julieta Nattero (Public Library of Science (PLoS), 2022)
Background Chagas is a complex and multidimensional socio-environmental health phenomenon, in which different components converge and interact. Historically, this disease was associated with insect vectors found in the rural environment. However, in the Americas, we are currently facing a new paradigm, in which different scenarios allow maintaining the vectorial transmission of the parasite through triatomine populations that either occasionally enter the dwellings or colonize urban environments. Methodology/principal findings Records of scientific reports available in the PubMed and LILACS search engines were retrieved, using three criteria according to the main triatomine genera of epidemiological importance and to the general scientific production on Chagas disease in urban contexts. Results showed that records on the occurrence of vectors in urban dwellings began to increase in the last three decades. Results also showed that the main species of triatomines collected inside dwellings (18 in total) belong mainly to the genera Triatoma and Panstrongylus, with most species (16/18, 88.8%) infected with the parasite, and that infestation of triatomine species occurs in all types of cities (small, medium and large, including megalopolises), from Argentina to the USA. Conclusions/significance Urban Chagas represents a new challenge that adds a different dimension to the problem of Chagas disease due to the particular characteristics of the lifestyle in urban agglomerates. The new scenario will require adaptations of the programs of control of vector to this shift from rural to urban settlements.